Putting family first as a boundary management tactic. Issue 1 (5th January 2021) - Thompson, Merideth; Carlson, Dawn S.; Kacmar, K. Michele
Abstract : Purpose: The authors examine a boundary management tactic for managing the work–family interface: putting family first (PFF). PFF is a boundary management tactic defined as the voluntary behavior of intentionally putting family obligations ahead of work obligations in a way that violates organizational norms Design/methodology/approach: In Study 1, The authors develop a theoretically derived measure of PFF and distinguish it theoretically and empirically from similar existing constructs, examining convergent and discriminate validity to demonstrate its uniqueness. In Study 2, the authors demonstrate PFF's predictive validity beyond the job incumbent using a three-way matched sample of 226 individuals, including the job incumbent's coworker and spouse. Findings: The authors established and validated a measure of PFF, developing and replicating the nomological network. PFF crossed over to positively relate to coworker role overload, job frustration and work–family conflict and to spousal stress transmission and relationship tension. Similarly, PFF related negatively to spousal family satisfaction and organizational commitment. Originality/value: The authors extend the work–family and boundary management literatures by proposing a new form of boundary management, PFF, which is a tactic for managing the work–family interface, and explore how its use influences not only the job incumbent but also the coworker and the spouse.